Exploring the role of Population density and Housing to achieve Sustainable Urban Growth - A Case of Hyderabad, India - Baksh, Shaheena; Ramaraj, Arulmalar (MAJ - Malaysia Architectural Journal, 2025)
The global phenomenon is characterized by a city population growth and the corresponding urbanization growth. As more people move from rural areas to cities, it becomes very essential to manage the urban development of cities. However, the Nation’s unsustainability is lower than that of other major countries. The urban area must be sustained as the city expands globally. The objective of the paper is to explore the role of population density and housing to achieve sustainable urban growth in the study area, of Hyderabad. This paper is likely to investigate the interplay between density and housing and analyze how population density and housing contribute to achieving sustainable urban development. Data is collected from secondary resources. The findings suggest that effective and inclusive planning is essential to address the challenges faced by policymakers, urban planners, urban designers, and stakeholders, and recommend that they adopt a comprehensive and responsible approach to leverage the advantages of city density and housing for a sustainable future of Indian cities.